2021
DOI: 10.1021/acs.molpharmaceut.0c01174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Species on Maximum Aqueous Phase Supersaturation Revealed by Quantitative Nuclear Magnetic Resonance Spectroscopy

Abstract: The polymer used in an amorphous solid dispersion (ASD) formulation impacts the maximum achievable drug supersaturation. Herein, the effect of dissolved polymer on drug concentration in the aqueous phase when a drug-rich phase was generated by liquid−liquid phase separation (LLPS) was investigated for different polymers at various concentrations of drug and polymer. Solution nuclear magnetic resonance (NMR) spectroscopy revealed that polyvinylpyrrolidone (PVP), polyvinylpyrrolidone/vinyl acetate (PVP-VA), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 59 publications
6
33
0
Order By: Relevance
“…The mixing of the polymer with the IBP-rich phase caused these peak shifts. , Indeed, the polymer peak intensity in the aqueous phase decreased in the presence of the IBP-rich phase (Figure S3). The 1 H peaks of the polymer present in the IBP-rich phase cannot be detected in the solution-state NMR spectrum due to the long re-orientational correlation time of the polymer in this phase . The mixing of polymer with the IBP-rich phase also resulted in mobility suppression of IBP in the drug-rich phase, together with changes in the chemical environment of IBP molecules in this phase.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The mixing of the polymer with the IBP-rich phase caused these peak shifts. , Indeed, the polymer peak intensity in the aqueous phase decreased in the presence of the IBP-rich phase (Figure S3). The 1 H peaks of the polymer present in the IBP-rich phase cannot be detected in the solution-state NMR spectrum due to the long re-orientational correlation time of the polymer in this phase . The mixing of polymer with the IBP-rich phase also resulted in mobility suppression of IBP in the drug-rich phase, together with changes in the chemical environment of IBP molecules in this phase.…”
Section: Resultssupporting
confidence: 91%
“…Thus, these polymers at a concentration of 1000 μg/mL showed a minimal solubilization effect on IBP. This result is in agreement with a previous study which reported that the molecular state of aqueous phase dissolved IBP was unchanged by adding PVP, PVP–VA, or HPMC at 1000 μg/mL …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solubilities of amorphous acalabrutinib dosed as the 50/50 ( w/w ) acalabrutinib/HPMCAS-H ASD were determined in different HCl molarities (pH 4.0, 4.5, 5.0, and 6.0) containing 34 mM NaCl. This approach was used rather than measuring amorphous solubility in the absence of polymer, since polymer has been shown to impact the apparent amorphous solubility [ 13 , 31 ]. After dosing the 50/50 ( w/w ) acalabrutinib/HPMCAS-H ASD to each medium, HCl was automatically titrated to maintain the target starting pH during dissolution using a Metrohm Titrado apparatus (Metohm, Tampa, FL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…58,59 Furthermore, a previous study has shown that polymer partitioning from the aqueous phase into the drug-rich phase formed in drug-supersaturated solutions varies depending on the molecular weight of the polymer; higher molecular weights of PVP and HPMC resulted in greater polymer partitioning into the drug-rich phase. 60 Similarly, the distribution of additives in CLT self-associates can increase with an increase in the molecular weight of NEP and PVP. Thus, an increase in the molecular weight of the additives resulted in a stronger mobility suppression of CLT self-associates.…”
Section: ■ Discussionmentioning
confidence: 99%